Financial Distress on Islamic Banks in Indonesia Impact of Covid 19 Pandemic and Economic Recession - Shafitranata, Shafitranata; Octavia, Ria (Penerbit Goodwood, 2025)
Purpose: The aim of this research is to identify and analyze the financial distress of Islamic banks in Indonesia during the pandemic and economic recession through an assessment of NPF, FDR, GCG, ROA, CAR, bank size, inflation, and interest rates. This research uses Islamic bank panel data for 2018-2022 and is quantitative research.Methodology/approach: Data analysis using Stata 17, through panel data regression and the data analysis method in this study using Ordinary Least Square (OLS). Population of this research is 10 Islamic banks in Indonesia with a total observation of 50 firm-years and the data used are secondary data of annual reports of Islamic banks. Results/findings: The findings show that the financial distress of Islamic banks is influenced by FDR, ROA, and CAR, and is not influenced by NPF, GCG, bank size, inflation, and interest rates. Islamic banks must carry out efficiency, restructuring, and manage the capital adequacy ratio so that it does not have an impact on the company's financial performance.Conclusions: The financial distress in Islamic banks in Indonesia during the COVID-19 pandemic and economic recession is significantly affected by the Financing to Deposit Ratio (FDR), Return on Assets (ROA), and Capital Adequacy Ratio (CAR). Limitations: The limitations of the study are that the sector studied is only Islamic banks in Indonesia so that the variables that influence are not comprehensive, allowing other variables to play a role in the financial distress of Islamic banks in Indonesia.Contribution: This research contributes by analyzing the performance of Islamic banks in Indonesia during the COVID-19 pandemic and in the face of economic recession. The widespread impact across various sectors, particularly the financial sector, underscores the need for government support through policies and regulations to ensure the stability of Islamic banks.